Collaborative Governance dalam Pengembangan Desa Wisata Nagari Tuo Pariangan pada Tahun 2021-2022 - Moreta, Adinda; Harirah MS, Zulfa (Journal of Social and Policy Issues, 2023)
Nagari Tuo Pariangan Tourism Village is one of the tourism areas in Tanah Datar Regency which has been affected by the COVID-19 pandemic. Interestingly, in 2021-2022 it has managed to rise followed by several achievements, namely being in the ADWI 2022 Top 50 category, 1st Place for Developing Tourism Villages and obtaining 2 MURI Records, namely the First Tourism Village with Coffee-Scented Batik and the First Tourism Village with Batik Coloring Experience from Coffee Waste in the ADWI 2022 event. The purpose of this research is to find out how collaborative governance has been carried out so that the Nagari Tuo Pariangan Tourism Village has succeeded in reviving quickly which is studied using the Collaborative Governance Regime (CGR) theory from Emerson, Nabatchi, & Balogh (2012). This research uses a qualitative approach with a descriptive research type and is located in the Nagari Tuo Pariangan Tourism Village. The entire data was obtained through interviews with 17 informants, observations, and documentation which were analyzed using qualitative data analysis stages according to Miles and Huberman. The results of the study show that the dynamics of collaboration have not fully gone well because not all people understand that their area is a tourist destination. Nonetheless, other parties involved have carried out their roles and duties properly which have had an impact on increasing the number of tourist visits and some positive impacts felt by certain communities. The increase in the number of tourist visits must be balanced with the availability of homestays which are currently still limited and given that the majority of tourism revenue comes from guests staying overnight. This is a temporary adaptation which will later be used as a correction for the next collaboration. It can be concluded that collaborative governance in the development of the Nagari Tuo Pariangan Tourism Village has not fully run optimally.